Health Literacy and Medication Adherence among Patients with Hypertension - Lenggogeni, Devia Putri; Yeni, Fitra; Malini, Hema; Anyati, Reffy (Jurnal Keperawatan Soedirman, 2024)
Hypertension requires patients to adhere to a medication regimen that needs to be adhered to for life to control blood pressure and prevent complications. A related factor to medication adherence is patients' health literacy, which influences their ability to maintain hypertension prescription regimens. This factor is critical in managing chronic diseases, such as hypertension, to achieve optimal health. This study aims to investigate the relationship between health literacy and medication adherence in patients with hypertension. The study was conducted at public health care centers in West Sumatra. This study used a quantitative approach with a cross-sectional design. The researchers used a non-probability sampling technique, namely purposive sampling, for a total sample of 175 respondents. Data were collected using the Morisky Medication Adherence (MMAS-8) and Health Literacy Survey Europe-16 (HLS-EU-Q16) questionnaires. Data were processed using computerization with chi-square test. The results showed that 41.7% of patients with hypertension have sufficient health literacy, and 46.9% have low levels of medication adherence. In addition, 52.3% with inadequate health literacy had low levels of medication adherence. The statistical test results obtained a p-value = 0.001 (p < 0.005), indicating a relationship between health literacy and medication adherence. It is essential to improve hypertension treatment adherence by improving the health literacy of patients with hypertension.